Weight-based firefly algorithm for document clustering - Mohammed, Athraa Jasim; Yusof, Yuhanis; Husni, Husniza (Springer, 2013)
Existing clustering techniques have many drawbacks and this includes being trapped in a local optima. In this paper, we introduce the utilization of a new meta-heuristics algorithm, namely the Firefly algorithm (FA) to increase solution diversity. FA is a nature-inspired algorithm that is used in many optimization problems.The FA is realized in document clustering by executing it on Reuters-21578 database.The algorithm identifies documents that has the highest light intensity in a search space and represents it as a centroid.This is followed by recognizing similar documents using the cosine similarity function.Documents that are similar to the centroid are located into one cluster and dissimilar in the other.Experiments performed on the chosen dataset produce high values of Purity and F-measure.Hence, suggesting that the proposed Firefly algorithm is a possible approach in document clustering.